Identification of vascular and hematopoietic genes downstream of etsrp by deep sequencing in zebrafish. - Gustavo Gomez; Jae-Hyung Lee; Matthew B Veldman; Jing Lu; Xinshu Xiao; Shuo Lin (PLoS ONE)
The transcription factor etsrp/Er71/Etv2 is a master control gene for vasculogenesis in all species studied to date. It is also required for hematopoiesis in zebrafish and mice. Several novel genes expressed in vasculature have been identified through transcriptional profiling of zebrafish embryos overexpressing etsrp by microarrays. Here we re-examined this transcriptional profile by Illumina RNA-sequencing technology, revealing a substantially increased number of candidate genes regulated by etsrp. Expression studies of 50 selected candidate genes from this dataset resulted in the identification of 39 new genes that are expressed in vascular cells. Regulation of these genes by etsrp was confirmed by their ectopic induction in etsrp overexpressing and decreased expression in etsrp deficient embryos. Our studies demonstrate the effectiveness of the RNA-sequencing technology to identify biologically relevant genes in zebrfish and produced a comprehensive profile of genes previously unexplored in vascular endothelial cell biology.